LEGAL ANALYSIS OF CORRUPTION CASES SOCIAL ASSISTANCE THE MINISTER OF SOCIAL RESPONSIBILITY BASED ON THE CRIMINAL ACTION OF CORRUPTION AND ITS IMPACTS - Ida Ayu Gede Mirah Saskarayani; Kadek Krisna Puspawati (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2021)
This article is intended to find out and examine the news that is currently being discussed, namely the corruption case of the social minister for social assistance provided to citizens affected by Covid 19. A social minister named Juliari Batubara was officially named a suspect by the Corruption Eradication Commission (KPK). The former Minister of Social Affairs Juliari was caught for corrupting social assistance funds from the government that were supposed to be used to help people affected by the Covid 19 pandemic. Social assistance that should be for the community is instead kept alone to enrich and support their families. Even the funds that were corrupted were not small, amounting to approximately Rp. 17 billion. The money confiscated by the KPK which was used as evidence also had suitcases. How can the minister of social corruption, social assistance, which is supposed to be for the daily lives of the difficult people who are affected by Covid 19. Like not having any sense of empathy because what is being corrupted is social assistance. Many famous people were very angry with this former social minister.